The market value of control in publicly-traded corporations - Lease, Ronald C.; McConnell, John J.; Mikkelson, Wayne H. (Journal of Financial Economics, 1983)
This paper tests the hypothesis that the future distribution of payoffs provided by a common stock depends upon whether ownership of the stock also conveys control over the firm's activities. For 26 firms that had two classes of common stock outstanding, the class with superior voting rights traded at a premium relative to the other class. However, in four firms where the ownership structure of the firm also included a class of voting preferred stock, the class of common with superior voting rights traded at a significant discount relative to the class of common with inferior voting rights. The analysis suggests that there are both benefits and costs of corporate control.